Teachers' Teaching Quality in Improving Learning Quality - Kurniati, Firzayuni; Fitria, Happy; Wahidy, Achmad (Journal of Social Work and Science Education, 2022)
The goal of this study was to evaluate and analyze: (1) the effectiveness of teachers in increasing the quality of learning at MTs Darussalam Lahat; (2) the barriers encountered by teachers; and (3) the approach applied. This is a qualitative research method using a descriptive approach. The following data gathering methods were used: (1) observation; (2) interviews; and (3) documentation. Techniques for analyzing research data include (1) data reduction; (2) data presentation; and (3) data verification/conclusion. According to the findings of the study, (1) teachers are capable of planning classes, carrying out learning, evaluating learning, following up on the learning outcomes supplied, and providing advice and counseling; (2) due to restricted facilities, not all instructors can participate in activities such as training, MGMP, and seminars. (3) the technique adopted by teaching teachers to improve the quality of learning at MTs Darussalam Lahat is to seek infrastructure that is not already present in schools, such as multiplying books as learning medium to fulfill the learning demands of students.